RELIGIOUS MODERATION IN INDONESIA: GOVERNMENT AND COMMUNITY ORGANIZATION INITIATIVES IN FOSTERING TOLERANCE AMONG RELIGIOUS COMMUNITIES - Loso Judijanto; Mochamad Gilang A Mubarok; Cut Ita Erliana, Defi Irwansyah, Dahlan Abdullah (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
This research delves into the multifaceted landscape of religious moderation in Indonesia, specifically examining the initiatives undertaken by both the government and community organizations to foster tolerance among diverse religious communities. Indonesia, renowned for its rich religious diversity, faces the dual challenge of celebrating its Islamic heritage while ensuring inclusivity for minority religious groups. Against this backdrop, our study employs a mixed- methods approach, combining qualitative, in-depth interviews, surveys, and case studies to gain comprehensive insights. The qualitative arm involves interviews with key stakeholders, including government officials, religious leaders, and community representatives. These interviews aim to uncover the lived experiences, challenges, and successes in fostering religious moderation. Complementing this, surveys provide quantitative data, gauging public perceptions and the effectiveness of existing initiatives. Diverse case studies contribute contextual depth, offering a nuanced understanding of specific instances. Sampling techniques ensure representation from various religious communities and regions, fostering inclusivity in data collection. Ethical considerations, including informed consent and ethical review, underpin our commitment  to  respecting  participants'  rights.  The  analysis  incorporates quantitative and qualitative approaches, employing statistical tools and thematic analysis to discern patterns and insights. This research aims to contribute to Indonesia's ongoing discourse on religious harmony by elucidating the dynamic interplay between government policies and grassroots efforts